Cnr2 Is Important for Ribbon Synapse Maturation and Function in Hair Cells and Photoreceptors - Colón-Cruz, Luis; Rodriguez-Morales, Roberto; Santana-Cruz, Alexis; Cantres-Velez, Juan; Torrado-Tapias, Aranza; Lin, Sheng-Jia; Yudowski, Guillermo; Kensler, Robert; Marie, Bruno; Burgess, Shawn M.; Renaud, Olivier; Varshney, Gaurav K.; et al. (Frontiers in Molecular Neuroscience, 2021)
The role of the cannabinoid receptor 2 (CNR2) is still poorly described in sensory epithelia. We found strong cnr2 expression in hair cells (HCs) of the inner ear and the lateral line (LL), a superficial sensory structure in fish. Next, we demonstrated that sensory synapses in HCs were severely perturbed in larvae lacking cnr2. Appearance and distribution of presynaptic ribbons and calcium channels (Cav1.3) were profoundly altered in mutant animals. Clustering of membrane-associated guanylate kinase (MAGUK) in post-synaptic densities (PSDs) was also heavily affected, suggesting a role for cnr2 for maintaining the sensory synapse. Furthermore, vesicular trafficking in HCs was strongly perturbed suggesting a retrograde action of the endocannabinoid system (ECs) via cnr2 that was modulating HC mechanotransduction. We found similar perturbations in retinal ribbon synapses. Finally, we showed that larval swimming behaviors after sound and light stimulations were significantly different in mutant animals. Thus, we propose that cnr2 is critical for the processing of sensory information in the developing larva